Radiative Collapse in Plasma Focus Operated with Heavy Noble Gases - Akel, M.; Lee, S. (Springer US, 2013)
Numerical experiments were carried out using 5-phase Lee model on different plasma focus devices with different filling gases. The relation of radiation power gain/loss terms as a function of temperature has been demonstrated. Variation of radial trajectories versus pressure with 0.1 Torr step has been investigated. Radiative collapse phenomena in plasma focus devices have been observed for heavy noble gases (Ar, Kr, Xe). Obtained results showed that the line radiation emission and tube voltage have huge values near the radiative collapse regime.